Climate Change and Agriculture in Latin America, 2020-2050 : Projected Impacts and Response to Adaptation Strategies - Fernandes, Erick C.M.; Soliman, Ayat; Confalonieri, Roberto; Donatelli, Marcello; Tubiello, Francesco (World Bank, Washington, DC, 2013)
The impacts of climate change on agriculture are projected to be significant in coming decades, so response strategies, and their likely costs, should be evaluated now. That is why this study produced an open-access, crop-climate-economic impact modeling platform for Latin America and the Caribbean, that can be extended to other regions, then modified and improved by users as new crop, climate, and economic datasets become available. The new platform projects the likely impacts of agroclimatic factors on crop productivity, on the basis of climate projections from two general circulation models, and couples it with an economic model to derive and evaluate a range of climate-change scenarios and likely agricultural productivity and economic impacts over the next several decades.